2005
DOI: 10.2337/diabetes.54.5.1340
|View full text |Cite
|
Sign up to set email alerts
|

A Role for iNOS in Fasting Hyperglycemia and Impaired Insulin Signaling in the Liver of Obese Diabetic Mice

Abstract: Chronic inflammation has been postulated to play an important role in the pathogenesis of insulin resistance. Inducible nitric oxide synthase (iNOS) has been implicated in many human diseases associated with inflammation. iNOS deficiency was shown to prevent high-fat diet-induced insulin resistance in skeletal muscle but not in the liver. A role for iNOS in fasting hyperglycemia and hepatic insulin resistance, however, remains to be investigated in obesity-related diabetes. To address this issue, we examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
179
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(194 citation statements)
references
References 51 publications
11
179
1
3
Order By: Relevance
“…In agreement with our previous studies 26 , iNOS disruption in ob/ob mice caused a reduction in body weight as well as an improvement in glucose and lipid metabolism as compared to ob/ob counterparts. Although a large controversy exists on the role of iNOS on glucose homeostasis, [40][41][42] our results are in agreement with our previous studies 26 . In order to analyze the impact of the absence of iNOS on AT in ob/ob mice, markers of adipogenesis (Pparg, Fasn, and Cidec) and fat browning (Prdm16 and Ucp1) were evaluated.…”
Section: Resultssupporting
confidence: 83%
“…In agreement with our previous studies 26 , iNOS disruption in ob/ob mice caused a reduction in body weight as well as an improvement in glucose and lipid metabolism as compared to ob/ob counterparts. Although a large controversy exists on the role of iNOS on glucose homeostasis, [40][41][42] our results are in agreement with our previous studies 26 . In order to analyze the impact of the absence of iNOS on AT in ob/ob mice, markers of adipogenesis (Pparg, Fasn, and Cidec) and fat browning (Prdm16 and Ucp1) were evaluated.…”
Section: Resultssupporting
confidence: 83%
“…This inhibition has implications in conditions such as diabetes, insulin resistance, and Alzheimer's disease. Increased inflammation and the elevated production of NO have been shown to affect insulin clearance and processing, which contributes to overall insulin resistance [29,30]. Enhanced expression of iNOS as a result of inflammation is a factor in insulin resistance, and depletion of iNOS has been shown to enhance insulin sensitivity [7,8,29].…”
Section: Discussionmentioning
confidence: 99%
“…Increased inflammation and the elevated production of NO have been shown to affect insulin clearance and processing, which contributes to overall insulin resistance [29,30]. Enhanced expression of iNOS as a result of inflammation is a factor in insulin resistance, and depletion of iNOS has been shown to enhance insulin sensitivity [7,8,29]. A large body of literature has shown that inflammation and insulin resistance may be underlying causes in the development of Alzheimer's disease as well [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the infusion of the arginine analogue L-NG-nitroarginine methyl ester (L-NAME) raised blood pressure but had no effect on fasting hepatic glucose production [10]. Other studies showing a direct role of NO in inducing hepatic insulin resistance have used models in which excess NO was generated through liver-specific overexpression of the inducible nitric oxide synthase (NOS) isoform [11]. In liver homogenates, NO has recently been shown to dosedependently inhibit the specific protease insulin-degrading enzyme (IDE), which is largely responsible for whole-body insulin clearance [12].…”
Section: Introductionmentioning
confidence: 99%